Pigbel-like syndrome in a vegetarian in Oxford. Issue 2 (August 1996) - Farrant, J M; Traill, Z; Conlon, C; Warren, B; Mortensen, N; Gleeson, F V; Jewell, D P
Abstract : Enterocolitis necroticans or pigbel is a rare condition characteristically affecting chronically malnourished people who abruptly increase their intake of protein. The classic presentation of the disease as seen in the highlands of Papua New Guinea is that of a necrotising enterocolitis after the ritual ingestion of contaminated pork. In this context, the presentation of the same disease in a well nourished white vegetarian in Oxford was all the more intriguing.